Protein- and Peptide-Based Virus Inactivators: Inactivating Viruses Before Their Entry Into Cells - Su, Xiaojie; Wang, Qian; Wen, Yumei; Jiang, Shibo; Lu, Lu (Frontiers in Microbiology, 2020)
Infectious diseases caused by human immunodeficiency virus (HIV) and other highly pathogenic enveloped viruses, have threatened the global public health. Most antiviral drugs act as passive defenders to inhibit viral replication inside the cell, while a few of them function as gate keepers to combat viruses outside the cell, including fusion inhibitors, e.g., enfuvirtide, and receptor antagonists, e.g., maraviroc, as well as virus inactivators (including attachment inhibitors). Different from fusion inhibitors and receptor antagonists that must act in the presence of target cells, virus inactivators can actively inactivate cell-free virions in the blood, through interaction with one or more sites in the envelope glycoproteins (Envs) on virions. Notably, a number of protein- and peptide-based virus inactivators (PPVIs) under development are expected to have a better utilization rate than the current antiviral drugs and be safer for in vivo human application than the chemical-based virus inactivators. Here we have highlighted recent progress in developing PPVIs against several important enveloped viruses, including HIV, influenza virus, Zika virus (ZIKV), dengue virus (DENV), and herpes simplex virus (HSV), and the potential use of PPVIs for urgent treatment of infection by newly emerging or re-emerging viruses.